Ice age. Collision course [videorecording (DVD)] - Romano, Ray; Leary, Denis; Leguizamo, John (Twentieth Century Fox Home Entertainment, 2016)
Scrat's epic pursuit of the elusive acorn catapults him into the universe where he accidentally sets off a series of cosmic events that transform and threaten the Ice Age World. To save themselves, Sid, Manny, Diego, and the rest of the herd must leave their home and embark on a quest full of comedy and adventure, traveling to exotic new lands and encountering a host of colorful new characters.